Property rating potentials and hurdles: what can be done to boost property rating in Ghana? (Commonwealth Journal of Local Governance, 2015)
Population growth in many of Africa’s towns and cities has outpaced local authority capacity to provide efficient management, infrastructure and financing. There is already debate over the capability and capacity of urban local governments to provide basic services to a growing population, due to budget constraints and inability to raise the required local-level revenue. This paper looks at how the potential of property rating can be harnessed to generate the bulk of revenue needed for local-level development, despite the huge default rates across Ghana. Focusing on Wa Municipality as a case study, the study finds that the major hurdles to property rating are poor property data systems, political interference, non-enforcement of the law, low budget deficit in financing revaluation, insufficient staffing, and insufficient technical capacity of the few staff available at the municipal valuation and rating divisions. Despite these constraints, however, field data still indicates that property rating in Ghana, and especially in Wa Municipality, can generate up to 30% of local government revenue needed. This is conditional on streamlining current challenges and improving resources for the rating and valuation units. There is extensive non-payment of property rates in Wa Municipality due to lack of awareness of the purpose of this tax, of how to pay and of the penalties for defaulting payees.